Energy Efficient Parallel K-Means Clustering for an Intel® Hybrid Multi-Chip Package - Souza, Matheus A.; Maciel, Lucas A.; Penna, Pedro Henrique; Freitas, Henrique C. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2018: Anais do XXX International Symposium on Computer Architecture and High Performance Computing, 2018)
FPGA devices have been proving to be good candidates to accelerate applications from different research topics. For instance, machine learning applications such as K-Means clustering usually relies on large amount of data to be processed, and, despite the performance offered by other architectures, FPGAs can offer better energy efficiency. With that in mind, Intel has launched a platform that integrates a multicore and an FPGA in the same package, enabling low latency and coherent fine-grained data offload. In this paper, we present a parallel implementation of the K-Means clustering algorithm, for this novel platform, using OpenCL language, and compared it against other platforms. We found that the CPU+FPGA platform was more energy efficient than the CPU-only approach from 70.71% to 85.92%, with Standard and Tiny input sizes respectively, and up to 68.21% of performance improvement was obtained with Tiny input size. Furthermore, it was up to 7.2×more energy efficient than an Intel® Xeon Phi ™, 21.5×than a cluster of Raspberry Pi boards, and 3.8×than the low-power MPPA-256 architecture, when the Standard input size was used.